Six Eclogues from William Barnes's Poems of Rural Life in the Dorset Dialect (First Collection, 1844) - L. Burton, T. (University of Adelaide Press, 2011)
When William Barnes began publishing poems in the Dorset County Chronicle in the 1830s in the dialect of his native Blackmore Vale, the first poems that appeared were in the form of eclogues - dialogues between country people on country matters. Although an immediate success, the eclogues were in time overshadowed by the many lyric poems that Barnes published in the dialect. They are now perhaps the most undervalued works by this brilliant but neglected poet. Each eclogue is, effectively, a one-scene play, demanding performance for its potential to be realized. The phonemic transcripts in this book, based on the findings in T. L. Burton's William Barnes's Dialect Poems: A Pronunciation Guide (2010), show what the poems would have sounded like in Barnes's own time; the accompanying audio recordings (made at the 2010 Adelaide Fringe) give living voice to the sounds noted in the transcripts.